(untitled) (Gumilyov Journal of Pedagogy, 2026)
The article examines the issue of conscious choice of minor programs within the higher education system of the Republic of Kazakhstan in the context of implementing flexible and individualized educational trajectories. Although minor programs are widely used as a tool for expanding students’ professional competencies, their selection is often formal and lacks reflective consideration of educational and career implications. The purpose of the study is to substantiate the potential of the hermeneutic approach as a methodological foundation for supporting the choice of minor programs. The methodological framework of the study is based on the ideas of philosophical and pedagogical hermeneutics, as well as the principles of student-centered learning. The research employed methods of theoretical analysis, comparative analysis, survey research, statistical data processing, correlation analysis, and analysis of variance. The study was conducted through the analysis of regulatory documents, educational programs, student registration statistics, and the results of a sociological survey involving 1,968 students from universities in Kazakhstan. The findings indicate that the greatest interest among students was shown in the fields of “Software Development and Python” (21.5%) and “Artificial Intelligence and Machine Learning” (14.2%). The application of hermeneutic practices was associated with an increase in students’ awareness of their educational choices (M = 4.31 compared to M = 3.48 in the control group; p < 0.001) and an increase in average GPA by 0.24 points. The study concludes that the hermeneutic approach facilitates the transition from formal course selection to the conscious design of an individual educational trajectory.